Mitigation of Fouling in Plate Heat Exchangers for Process Industries - Kapustenko, P. O.; Tovazhnyanskyy, Leonid Leonidovich; Arsenyeva, O. P.; Yuzbashyan, A. P. (The Italian Association of Chemical Engineering, 2012)
Among different methods for mitigation of fouling the use of enhanced heat transfer surfaces is one of the major categories. Heat transfer enhancement is one of the main features of Plate Heat Exchanger (PHE) and mitigation of fouling render even more advantages to the use of this type of heat transfer equipment in different applications at process industries. In present study the period of fouling deposit formation in PHEs and influencing it factors are investigated. To estimate development of fouling thermal resistance with time the Equation is proposed. The pictures of fouling deposit distribution along the plate of PHE for fresh water heating are analyzed. The conclusion is, that for scaling fouling there exist some threshold conditions on wall shear stress, wall temperature and salt content, after which fouling deposition starts. The expression of fouling deposition rate proposed for the tubes with heat transfer enhancement by Yang and Crittenden is used. Comparison with available in literature experimental data have shown good agreement with proposed model, when one its parameter is adjusted. For certain cooling water circuit of a big industrial enterprise this parameter can be determined by data about fouling in one heat exchanger. After that the model can be used for prediction of cooling water fouling development with a time in all heat exchangers of this circuit.